2008
DOI: 10.1142/s0129167x08004893
|View full text |Cite
|
Sign up to set email alerts
|

ATTRACTING BASINS OF VOLUME PRESERVING AUTOMORPHISMS OF ℂk

Abstract: We study topological properties of attracting sets for automorphisms of C k . Our main result is that a generic volume preserving automorphism has a hyperbolic fixed point with a dense stable manifold. On the other hand, we show that an attracting set can only contain a neighborhood of the fixed point if it is an attracting fixed point. We will see that the latter does not hold in the non-autonomous setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Peters, Vivas, and Wold point out that polynomial automorphisms with an attracting fixed point at infinity are dense in Aut ω 0 (C n ) [17,Remark 3.1]. It follows that the residual subset of chaotic automorphisms has empty interior in Aut ω 0 (C n ).…”
mentioning
confidence: 99%
“…Peters, Vivas, and Wold point out that polynomial automorphisms with an attracting fixed point at infinity are dense in Aut ω 0 (C n ) [17,Remark 3.1]. It follows that the residual subset of chaotic automorphisms has empty interior in Aut ω 0 (C n ).…”
mentioning
confidence: 99%
“…The analogous statement was proved for volume preserving holomorphic automorphisms of C n in [11], and generalized to Stein manifolds with the volume density property in [2].…”
Section: Dense Stable Manifoldmentioning
confidence: 63%
“…For X = C n , n ≥ 2, with the standard volume form this was proved by Fornaess and Sibony [69], and the authors follow their approach. They also showed that a generic volume preserving automorphism has a hyperbolic fixed point whose stable manifold is dense in X, generalizing a result of Peters, Vivas, and Wold on C n [144]. In their second paper [25], they proved closing lemmas for automorphisms of a Stein manifold with the density property and for endomorphisms of an Oka Stein manifold.…”
Section: Stein Manifolds With the Density Property And Oka Manifoldsmentioning
confidence: 79%